The Heaven & Earth Grocery Store - McBride, James, 1957-; Hoffman, Dominic ([New York, NY] : Penguin Audio, 2023)
In 1972, when workers in Pottstown, Pennsylvania, were digging the foundations for a new development, the last thing they expected to find was a skeleton at the bottom of a well. Who the skeleton was and how it got there were two of the long-held secrets kept by the residents of Chicken Hill, the dilapidated neighborhood where immigrant Jews and African Americans lived side by side and shared ambitions and sorrows. Chicken Hill was where Moshe and Chona Ludlow lived when Moshe integrated his theater and where Chona ran the Heaven & Earth Grocery Store. When the state came looking for a deaf boy to institutionalize him, it was Chona and Nate Timblin, the Black janitor at Moshe's theater and the unofficial leader of the Black community on Chicken Hill, who worked together to keep the boy safe.
Title from web page.
new cdbk 2024 summer.
Read by Dominic Hoffman.
Keywords: Ku Klux Klan (1915- ) -- Fiction; Jews -- United States -- Fiction; African Americans -- Fiction; Deaf children -- Fiction; Ethnic neighborhoods -- Pennsylvania -- Pottstown -- Fiction; Murder -- Investigation -- Fiction; United States -- Ethnic relations -- Fiction; Audiobooks; Novels; Sound recordings; Historical fiction